Significant influence of fungi on coarse carbonaceous and potassium aerosols in a tropical rainforest. (March 2015) - Zhang, Zhisheng; Engling, Guenter; Zhang, Leiming; Kawamura, Kimitaka; Yang, Yihong; Tao, Jun; Zhang, Renjian; Chan, Chuen-yu; Li, Yide
Abstract Fungal spores are ubiquitous in the Earth's atmosphere, especially in the environment of tropical rainforests with intense biological activities. To assess the impact of fungi on chemical components of atmospheric aerosols at a Chinese tropical rainforest site, size-segregated fungal spore tracers (i.e. arabitol and mannitol) were measured along with major aerosol components, including carbonaceous species and water-soluble inorganic ions. The fungal spore tracers were found to be predominately associated with coarse particles, in which organic carbon (OC) and potassium (K+) were also present at significant levels. Enhanced amounts of fungal spore tracers were closely linked to rainfall events. Moreover, fungal spore tracers exhibited positive correlations with relative humidity and negative correlations with wind speed, temperature or radiation. The relationships between fungal spore tracers and meteorological factors are consistent with the emission features of actively discharged fungal spores, which are generally associated with sugar alcohols and by-products such as the inorganic ion K+. The excellent correlations between fungal spore tracers and OC or K+ in the coarse particles further suggested their common emission sources. Absolute principal factor analysis further identified fungi as the largest contributor to coarse OC and K+ (both at ∼66%) in this rainforest.